Rapid serum tube technology overcomes problems associated with use ofanticoagulants - Zhao, Kong-Nan (Array, 2019)
Failure to obtain complete blood clotting in serum is a common laboratory problem. Our aim was to determine whether snake prothrombinactivators are effective in clotting blood and producing quality serum for analyte measurement in anticoagulated patients.Materials and methods: Whole blood clotting was studied in a total of 64 blood samples (41 controls, 20 Warfarin patients, 3 anticoagulated patientsusing snake venom prothrombin activator (OsPA)) with plain tubes. Coagulation was analysed using a visual assay, Hyland-Clotek and thromboelastography.Healthy control blood was spiked with a range of anticoagulants to determine the effectiveness of OsPa-induced clotting. A pairedanalysis of a Dabigatran patient and a control investigated the effectiveness of the OsPA clotting tubes. Biochemical analytes (N = 31) were determinedfor 7 samples on chemistry and immunoassay analysers and compared with commercial tubes.Results: Snake venom prothrombin activators efficiently coagulated blood and plasma spiked with heparin and commonly used anticoagulants.Clotting was observed in the presence of anticoagulants whereas no clotting was observed in BDRST tubes containing 3 U/mL of heparin. Snake venomprothrombin activator enhanced heparinised blood clotting by shortening substantially the clotting time and improving significantly the strengthof the clot. Comparison of 31 analytes from the blood of five healthy and two anticoagulated participants gave very good agreement betweenthe analyte concentrations determined.Conclusions: Our results showed that the snake venom prothrombin activators OsPA and PtPA efficiently coagulated recalcified and fresh bloodswith or without added anticoagulants. These procoagulants produced high quality serum for accurate analyte measurement.